PENGARUH KONFLIK AGENCY : KOMPOSISI KEPEMILIKAN, KOMPENSASI MANAJEMEN DAN LEVERAGE TERHADAP PERMINTAAN JASA NONASSURANCE - Roza Mulyadi (Tirtayasa Ekonomika, 2019)
This study aims to determine the relationship between agency conflicts affect the demand for nonassurance services use. This study uses a proxy the composition of ownership, management  compensation and leverage  for  the agency conflicts. The data from this study using annual reports companies listed in Indonesia Stock Exchange (IDX). Collecting data using purposive sampling using the criteria for sampling so that 34 samples were found to be researched. This data using the software Statistical Product and Service Solutions (SPSS) version 20.0. The results of this study are as follows: First the composition of ownership is not related to the demand nonassurance services. Second compensation management relate to the demand nonassurance services. Third leverage is not related with the demand nonassurance services in Indonesia